FINANCING EFFICIENCY ANALYSIS USING DATA ENVELOPMENT ANALYSIS (DEA) APPROACH AT BANK ACEH SYARIAH - Mawaddah; Muttaqien; Rico Nur Ilham; Zulfan; Frengki Putra Ramansyah (PT. Radja Intercontinental Publishing, 2024)
This study aims to analyze the level of Financing Efficiency Using the Data Envelopment Analysis (DEA) Approach at Bank Aceh Syariah. This type of research is descriptive quantitative research. The data collection technique uses secondary data in the form of financial statements accessed through the official website www.bankaceh.co.id. The collected data is processed using the STATA 17 program. The population used in this study is all financial reports of Bank Aceh Syariah. The sampling technique in this study uses saturated samples, namely the entire population. This study uses two variables, namely input variables consisting of Third-Party Funds and Fixed Assets and Financing output variables. The data analysis method used in this study is Data Envelopment Analysis. The results of the study show that there is variation in the level of efficiency during the entire 2020-2023 Period of Bank Aceh Syariah. Some branches show a high level of efficiency with a DEA score of 1, while others show varying levels of inefficiency with different DEA scores. Overall, Bank Aceh Syariah has achieved fairly efficient circumstances where the fluctuations observed reflect variations in bank performance from year to year. Despite these fluctuations, Bank Aceh Syariah continues to show a relatively good level of efficiency throughout the period. The theoretical implication of this study is to increase understanding of how DEA techniques can be used to evaluate and compare financing efficiency between units or branches in a Sharia bank. The managerial implication of this study is to assist management in making strategic decisions related to resource allocation, setting internal policies, and developing more effective financing strategies. By optimizing efficiency, banks can improve competitiveness, quality of service to customers, and long-term financial sustainability. Additionally, this study can be used as a tool for periodic performance evaluation and monitoring, ensuring that banks continue to operate at maximum efficiency.